2022
DOI: 10.1097/scs.0000000000008790
|View full text |Cite
|
Sign up to set email alerts
|

Current Presurgical Infant Orthopedics Practices Among American Cleft Palate Association–Approved Cleft Teams in North America

Abstract: Presurgical infant orthopedic (PSIO) therapy has evolved in both its popularity and focus of treatment since its advent. Nasoalveolar molding, nasal elevators, the Latham appliance, lip taping, and passive plates are the modern treatment options offered by cleft teams. Many cleft surgeons also employ postsurgical nasal stenting (PSNS) after the primary lip repair procedure. The purpose of this study is to examine trends in current PSIO care as well as PSNS for the management of patients with cleft lip and pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Other institutions have reported higher rates of postsurgical stenting in patients who do not receive NAM, presumably because this population has an increased need for nasal shape retention. 6 In our experience, patients who do not undergo NAM tend to have a mild cleft deformity with a mild nasal deformity. The decision to use nostril retainers at our institution is made on postoperative week 3, after examination by the treating surgeon and orthodontist.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Other institutions have reported higher rates of postsurgical stenting in patients who do not receive NAM, presumably because this population has an increased need for nasal shape retention. 6 In our experience, patients who do not undergo NAM tend to have a mild cleft deformity with a mild nasal deformity. The decision to use nostril retainers at our institution is made on postoperative week 3, after examination by the treating surgeon and orthodontist.…”
Section: Discussionmentioning
confidence: 76%
“…[1][2][3] A recent survey study reported that over half of the American Cleft Palate-Craniofacial Association (ACPA)-approved cleft teams offer some type of PSIO as part of the cleft treatment protocol, with a majority of these centers utilizing nasoalveolar molding (NAM) therapy. [4][5][6] NAM has been shown to reduce cleft severity prior to primary surgical repair, facilitate gingivoperiosteoplasty (GPP) to decrease the need for secondary alveolar bone grafting, and improve lip and nasal form. [7][8][9][10][11] However, despite reported improvements in aesthetic, functional, and psychological outcomes secondary to NAM treatment, the ease of access to and utilization of NAM has remained a topic of debate.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in 2011 across 117 centers in the United States found that 37% of cleft teams offered NAM treatment (12). However, a subsequent survey showed that 68% of centers now provide NAM treatment (13). In India, a recent survey indicated that 25% of centers are routinely conducting NAM treatment (14).…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in 2011 across 117 centres in the USA found that 37% of cleft teams offered NAM treatment [ 12 ]. However, a subsequent survey showed that 68% of centres now provide NAM treatment [ 13 ]. In India, a recent survey indicated that 25% of centres are routinely conducting NAM treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%